Medication management in physical therapy: the contribution of pharmacy technicians to patient safety and adherence - Abdulrahman Mushbab Oudah Al-Ahmari1, Nasser Ayed Nasser Alshahrani2, Merai Awad Merai Alqahtani3, Mesfer Awadh Mari Alqahtani4, Mohammed Mushabab Awdah Al-Ahmari5, Nasser Abdullah Jarallah Almarzouq6, Ali Muhammad Abdullah Al-Shahrani7 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Medication management is a crucial aspect of patient care in physical therapy, as it plays a significant role in managing pain, inflammation, and other symptoms that may hinder rehabilitation progress. The collaboration between physical therapists and pharmacy technicians is essential to ensuring patient safety and adherence to prescribed medications. Technician pharmacists play a vital role in the medication management process by assisting in the preparation, dispensing, and monitoring of medications for physical therapy patients. They work closely with physical therapists to ensure that the prescribed medications are appropriate for the patient’s condition and are administered correctly. By working collaboratively, physical therapists and pharmacy technicians can help prevent medication errors, drug interactions, and adverse effects that may compromise patient safety. pharmacy technicians also play a key role in educating patients about their medications, including proper dosage, administration techniques, and potential side effects. Overall, the contribution of pharmacy technicians to medication management in physical therapy is essential for promoting patient safety and adherence to treatment plans.